Pulmonary stretch receptor activity in man: a comparison with dog and cat - Guz, A. (1971)
1. The `collision' technique has been shown to be suitable for recording orthodromic `A' fibre activity in a whole, functioning cervical vagus nerve. This activity predominantly arises from pulmonary stretch receptors. 2. The amount and frequency of discharge from pulmonary stretch receptors in man, dog and cat, have been shown to increase with inspiration and decrease with expiration—the larger the tidal volume, the greater the discharge. At the end-expiratory level in man and dog, a tonic stretch receptor discharge is present. The results in cat and dog are in broad agreement with older work using single fibre techniques. 3. The stretch receptor discharge in man may be greater for a given degree of lung `stretch' than in cat or dog. There is certainly a discharge during eupnoea in man, and this must be contrasted with the absence of a Hering—Breuer inflation reflex in adult anaesthetized man with lung inflations of the order of a eupnoeic tidal volume. Furthermore, man does not develop slow, deep breathing with bilateral vagal block. 4. Since the characteristics of the activity from pulmonary stretch receptors with eupnoea in man are similar to those seen in other species, it must be concluded that this activity does not reach the central threshold to affect the respiratory centre.